(untitled) (KYAMC Journal, 2018)
Diabetes mellitus during pregnancy (i.e., Gestational Diabetes Mellitus or GDM) has definite impact on maternal & fetal health. A woman is diagnosed with gestational diabetes specially when glucose intolerance continues beyond 24-28 weeks of gestation GDM needs to be specially considered, because it may often remain undiagnosed leading to abortion, miscarriage, fetal obesity, intra-uterine growth retardation (IUGR), intrauterine death (IUD) of fetus in addition to maternal morbidities & mortalities. Here we have reviewed in brief about the causes, pathophysiology, complications, risks, diagnosis, management, prevention etc. of GDM. KYAMC Journal Vol. 9, No.-2, July 2018, Page 81-86